On the distribution and conservation status of some Mediterranean species new for the flora of Montenegro - Stešević, Danijela; Stanišić-Vujačić, Milica; Milanović, Đorđije; Šilc, Urban (Hacquetia, 2024)
Investigations of dune habitats in Montenegro led to the discovery of 8 species and infraspecies taxa new for the country: Avellinia festucoides (Link) Valdés & H. Scholz, Corynephorus divaricatus (Pourr.) Breistr., Isoetes histrix Bor., Juncus tenuis Willd., Medicago doliata Carmign., Myosotis laxa Lehm. ssp. cespitosa (Schultz) Hyl. ex Nordh., Setaria parviflora (Poir.) Kerguélen, and Solenopsis laurentia ssp. gasparrinii (Tineo) Brullo. Of particular importance are Solenopsis laurentia ssp. gasparrinii and Isoetes histrix, the first of which has not yet been recorded in the southeastern part of the Adriatic, while the second is doubtfully reported for Albania. Since only one or a potentially small number of additional localities are expected in Montenegro, the following species are proposed as candidates for the national list of legally protected species: Isoetes histrix, Solenopsis laurentia ssp. gasparrinii, Avellinia festucoides and Corynephorus divaricatus. According to the IUCN criteria, the Isoetes histrix, Solenopsis laurentia ssp. gasparrinii and Corynephorus divaricatus are assessed as CR, while Avellinia festucoides as EN. Monitoring and eradication measures are proposed for alien species (Setaria parviflora and Juncus tenuis), especially for the second one, which is considered invasive in some countries.